Redesigning elastic full‐waveform inversion on the new Sunway architecture - Mengyuan Hua; Wubing Wan; Zhaoqi Sun; Zekun Yin; Puyu Xiong; Xiaohui Liu; Haodong Tian; Ping Gao; Weiguo Liu; Hua Wang; Wenlai Zhao; Zhenchun Huang (Engineering Reports)
Abstract IFOS3D is a three‐dimensional elastic full‐waveform inversion (EFWI) tool designed for high‐resolution estimation of the Earth's material properties within 3D subsurface structures. However, due to the significant computational costs associated with 3D EFWI, leveraging the computing power of a supercomputer for implementation is a logical choice. In this article, we introduce several innovative process‐level and thread‐level optimizations based on heterogeneous many‐core architectures in the new Sunway supercomputer, which is a powerful system globally. These optimizations encompass a process‐level communication overlapping strategy, thread‐level data partitioning and layout approaches, a remote memory access optimized master‐slave communication scheme, and a thread‐level data reuse and overlapping strategy. Through these optimizations, we achieve significant improvements in each iteration, with a kernel function speedup of approximately 59× and an overall program speedup of about 14×. Our findings demonstrate the ability of our proposed optimization strategies to overcome the computational challenges associated with 3D EFWI, providing a promising framework for future advancements in the field of subsurface imaging.